MIX MARRIAGE (CANON 1124) The Ecumenical Spirit and Pastoral Approaches - Pandego, Higianes Indro (LOGOS, 2019)
Mixed marriage on the canon 1124, the 1983 Code refers to the marriage between Catholic and non-Catholic persons, which means that both of the persons are baptized. So, it must be the Sacrament (see can. 1055 Â§2). The Second Vatican Council picked the view of the people of God up based on the dignity of baptism. Then the Council expressed the idea of (full) communion in which the Catholic Church and the other Churches and communities have a relationship. To it Thus, The Council fosters the ecumenical movement that develops the union between the Christians, more especially concerning mixed marriage.